2008
DOI: 10.1159/000181170
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Social Participation in Older Adults

Abstract: Background: Social participation refers to daily activities, such as personal care and mobility, and social roles, such as interpersonal relationships and leisure. Although restrictions in participation in normal aging have been recognized, little research has been done to study the coping strategies used to alleviate those restrictions. Objective: The objective of the present study was to explore the relationships between cognitive and behavioural coping strategies and the social participation of community-dw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 45 publications
1
24
0
2
Order By: Relevance
“…Several studies have shown that psychological factors affect the societal participation of patients with chronic diseases like rheumatic disorders, cardiovascular diseases, Alzheimer’s Disease, MS, and Spinal Cord Injury (Adler & Matthews, 1994; Cameron & Leventhal, 2003; Stanton et al, 2007; Stein & Baum, 2013). Psychological factors found to be related to societal participation include successful performance of adaptive tasks, adjustment to disability, maintenance of emotional balance, the absence of psychological disorders (Maes et al, 1996), coping styles (Demers et al, 2009; Kennedy et al, 2006; Levasseur & Couture, 2015; Lindwall et al, 2012; Peter et al, 2014), and appraisal (Barnwell & Kavanagh, 1997; Peter et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that psychological factors affect the societal participation of patients with chronic diseases like rheumatic disorders, cardiovascular diseases, Alzheimer’s Disease, MS, and Spinal Cord Injury (Adler & Matthews, 1994; Cameron & Leventhal, 2003; Stanton et al, 2007; Stein & Baum, 2013). Psychological factors found to be related to societal participation include successful performance of adaptive tasks, adjustment to disability, maintenance of emotional balance, the absence of psychological disorders (Maes et al, 1996), coping styles (Demers et al, 2009; Kennedy et al, 2006; Levasseur & Couture, 2015; Lindwall et al, 2012; Peter et al, 2014), and appraisal (Barnwell & Kavanagh, 1997; Peter et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…It appears that individuals frequently adopt certain coping preferences, and engage in particular behaviors across different situations (Endler & Parker, 1994). Consequently, the level of societal participation results from these prior coping processes (Demers et al, 2009; Kennedy et al, 2006; Levasseur & Couture, 2015; Lindwall et al, 2012; Middleton & Craig, 2008; Peter et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…These authors found that by participating in various activities such as gardening, cultural activity, and home-based activities, older adults developed the ability to cope well with their stressors and enhanced their health and well-being. As evidence, Demers, Robichaud, Gélinas, Noreau, and Desrosiers (2008) found that older adults used social activity participation, such as social gatherings, as a coping strategy and, as a result, they reduced the effect of stressful life events associated with age.…”
mentioning
confidence: 98%
“…Individuals with different demographic characteristics including sex, age, education level, and job have different ways of coping with stress (1). In 1984, Lazarus and Folkman (2) defined coping as a way of mediating the effects of stressors on the psychological and physical level.…”
mentioning
confidence: 99%